Redevelopment of Boat Terminal Kuala Besar, Kota Bharu, Kelantan: sustainable design approach using mixed mode system in a designated building - Razali, Sali Amalia; Sanusi, Aliyah Nur Zafirah; Denan, Zuraini (IIUM Press, 2024)
The Boat terminal Kuala Besar is mainly used by villagers who live near Kuala Besar Village as their primary source of income for activities like fishing and transferring goods. In addition, it serves as the mode of transportation to Tumpat Island for daily commutes and tourism purposes. Nevertheless, the boat terminal now lacks several necessary facilities, such as a proper ticket booth, a decent waiting space for passengers, a functioning jetty, an accessible public restroom, and a prayer room. The projects also focus on how to integrate the systematic plan layout into building programming. Nevertheless, there are some environmental damages to the river, such as erosion and low and rising water levels in the Kelantan. Therefore, the intention is to redevelop the existing Boat Terminal Kuala Besar to meet the needs and demand based on the large capacity of the visitors concerning their comfort and safety through a sustainable design approach by using a mixed-mode system in a designated building. It is also in line with 2035 Kota Bharu (MPKB-BRI) local planning, the Lembaga Kemajuan Ikan Malaysia (LKIM), Boat Terminal Kuala Besar will become an agrotourism destination that will increase in the number of visitors (https://mpkbbri.kelantan.gov.my, 2022).